Efficacy and safety of rituximab in neuromyelitis optica: Review of evidence - Etemadifar, Masoud (J Res Med Sci, 2017)
Neuromyelitis optica (NMO) is an autoimmune inflammatory disease of the central nervous system with preferential involvement in the optic nerve and spinal cord with a widespread spectrum of clinical features; multiple therapeutic agents have been used with different results. Recent evidence points to B-cell-mediated humoral immunity in the pathogenesis of NMO. Rituximab targets the CD20 antigen on B-cells. Treatment leads to profound B-cell depletion, principally over an antibody-dependent cell cytotoxicity mechanism. The aim of our study was to review clinical trials to elucidate the impact of rituximab on the relapse rate, Expanded Disability Status Scale (EDSS), and progression of disability in NMO. We performed a comprehensive review of all studies that evaluated clinical and paraclinical effects of rituximab on NMO. MEDLINE-PubMed, Web of Sciences, EMBASE, and Cochrane databases up to June 2016 included in our searches. In addition, reference lists from articles identified by search as well as a key review article to identify additional articles included in the study. Rituximab targets the CD20 antigen on B-cells and decreases attack frequency and severity in patients with NMO; however, it does not remove attacks, even when modifying treatment to achieve B-cell depletion. Most of the investigations revealed that EDSS significantly in all patients with rituximab treatment will be decreased after treatment with rituximab. No new or enlarged lesions or pathological gadolinium enhancement was observed in serial brain and spinal cord magnetic resonance imaging, except for those observed concomitantly with clinical relapses and the median length of spinal cord lesions was significantly reduced after therapy. Rituximab targets the CD20 antigen and decreases attack frequency and severity in patients with NMO.